2008
DOI: 10.1093/rheumatology/ken411
|View full text |Cite
|
Sign up to set email alerts
|

Mannose-binding lectin-low genotypes are associated with milder systemic and immunological disease expression in primary Sjogren's syndrome

Abstract: SS patients with MBL-low genotypes have a less pronounced systemic and immunological disease expression in comparison with those carrying MBL-sufficient genotypes. In primary SS, MBL deficiency may represent a protective factor against the development of more aggressive autoimmune damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 45 publications
0
12
1
1
Order By: Relevance
“…In this context, mice lacking such bridging molecules, such as MFG-e8, Mer or C1q are reported to develop lupus-like manifestations associated with inefficient removal of apoptotic cells [32] . In line to these observations, several quantitative and functional aberrations of the above opsonins have been described in SLE and SS patients, including hypocomplementemia, which is considered as one of the major immunological markers and of key clinical importance for both disorders [44] , [45] . In fact, an intact classical complement pathway is essential for the phagocytic removal of apoptotic cells [46] , whereas the deficient ApoCell-phagocytosis in SLE patients has been previously attributed to defective opsonization of apoptotic cells by aberrantly low levels of C1q, C3, and C4 complement proteins [17] .…”
Section: Discussionmentioning
confidence: 67%
“…In this context, mice lacking such bridging molecules, such as MFG-e8, Mer or C1q are reported to develop lupus-like manifestations associated with inefficient removal of apoptotic cells [32] . In line to these observations, several quantitative and functional aberrations of the above opsonins have been described in SLE and SS patients, including hypocomplementemia, which is considered as one of the major immunological markers and of key clinical importance for both disorders [44] , [45] . In fact, an intact classical complement pathway is essential for the phagocytic removal of apoptotic cells [46] , whereas the deficient ApoCell-phagocytosis in SLE patients has been previously attributed to defective opsonization of apoptotic cells by aberrantly low levels of C1q, C3, and C4 complement proteins [17] .…”
Section: Discussionmentioning
confidence: 67%
“…The first description of MASP2 polymorphisms was made in 2003 (Stengaard-Pedersen et al, 2003), in a patient with invasive pneumococcal infection and autoimmune disease who carried MASP2 p.D371 and p.D120G polymorphisms (in addition to MBL2 B allele). Since then, a few other studies have addressed the frequency and possible effect of MASP2 polymorphisms in different populations or patients (Thiel et al, 2006(Thiel et al, , 2007(Thiel et al, , 2009Horcajada et al, 2009;Ramos-Casals et al, 2009;Vallès et al, 2009;Wang et al, 2009;Ytting et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…RamosCasals et al suggested that in primary Sjogren syndrome patients, MBL deficiency may represent a protective factor against the development of more aggressive autoimmune damage, since those with MBL-low genotypes have a less pronounced systemic and immunological disease expression than those carrying MBL-sufficient genotypes [100].…”
Section: The Complement System and Primary Sjögren's Syndromementioning
confidence: 99%